LEAN BEHAVIOR IMPACT TOWARDS LEAN MANAGEMENT: A CASE STUDY - Hamouda, A.M.S; Puvanasvaran, A.P.; Norazlin, N.; Suk Fan, C. (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Lean behavior is an essential element to create a continuous improvement culture in the service organization. Meanwhile, continuous improvement is defined as the never-ending efforts for improvement involving everyone in organization. The purpose of this study is to evaluate the changes of behavior practices after the introduction of lean tools and to discuss on how lean behavior in developing the continuous improvement culture in an office environment. This study focuses on self-administered questionnaire method to obtain the real time data for the analysis of behavior practices. Ford Questionnaire is used and distributed to the employees of different management levels in Business Development and IT department. The obtained results are analyzed using the Statistical Package for the Social Sciences (SPSS) software. The same questionnaire survey is conducted after the introduction of lean tools. The expected outcomes of this study is to determine the level of lean behavior practices in the office department and to provide a clear understanding on some lean behavior practices that need to be nurtured among the employees in order to produce a healthy work environment.